Managerial Insight Development Program for Improving Performance and Scalability of Micro Batik Fashion Businesses - Damayanti, Vidya; Hermawan, Agus; Winarno, Agung (International Journal of Business, Law, and Education, 2025)
This community service research focuses on accelerating the managerial capabilities of ASTAGUNAKU, a batik fashion Micro, Small, and Medium Enterprise (MSME) from Blitar, Indonesia. The primary issue identified was a significant gap between the business's potential—supported by strong legality and technical competence—and its unstructured, intuition-based management practices, which severely hindered scalability and marketing effectiveness. This condition is common among artisan-based MSMEs, where superior product quality is often not matched by robust business management, creating structural barriers to growth. This study aims to transform ASTAGUNAKU from an intuition-led operation into a measurable and scalable business entity through a structured intervention. The method employed was the Managerial Insight Development Program (Program Pengembangan Wawasan Manajerial - PWM), a qualitative action research study conducted intensively over four months (September-December 2025). The program involved five sequential phases: needs identification through diagnostic interviews, SWOT analysis to map strategic position, practical solution formulation, hands-on training workshops, and intensive mentoring for masterplan development. The program's results demonstrated significant improvements in three core areas: finance, with the complete separation of personal and business assets and the standardization of Cost of Goods Sold (COGS) calculation using digital bookkeeping; operations, through the creation and implementation of visual Standard Operating Procedures (SOPs) for production and quality control; and marketing, by successfully expanding sales channels to major marketplaces and launching an official website, leading to initial sales from these new channels. It is concluded that the PWM program successfully built a solid managerial foundation, effectively shifting ASTAGUNAKU from an intuitive craft-based enterprise to a structured micro-business poised for strategic expansion and sustainable growth.